10w - 8 + 6 - 4w = 6 w - 2
2 ( 3 w - 1 ) = 2 ∙ 3 w + 2 ∙ ( - 1 ) = 6 w - 2
Correct
( 6 w + 3 ) + ( 2 w - 7 ) =
6 w + 3 + 2 w - 7 = 8 w - 4
Incorrect
6w - 2 = 6w - 2
Correct
( 11 w - 1 ) - ( 5 w + 3 ) =
11 w - 1 - 5 w + 3 = 6 w + 2
Incorrect
3 w + 7 + 3 w - 9 = 6 w - 2
Correct
14w + 14 ≠ 6 w - 2
Incorrect
2 ( 5 w + 7 ) = 2 ∙ 5 w + 2 ∙ 7 = 10 w + 14
Incorrect
All the expressions that are equivalent to 10w - 8 + 6 - 4w:
2 ( 3 w - 1 ) , 6w - 2 , 3 w + 7 + 3 w - 9
Select all the expressions that are equivalent to 10w - 8 + 6 - 4w.
2(3w - 1)
(6w + 3) + (2w - 7)
6w - 2
(11w - 1) - (5w + 3)
3w + 7 + 3w - 9
14w + 14
2(5w + 7)
1 answer